061 Management of NMDA-receptor encephalitis on the neurological ICU. Issue 12 (14th November 2019) - Brown, Rachel; Spillane, Jennifer; Lunn, Michael; Radcliffe, Jeremy; Zandi, Michael; Kullmann, Dimitri; Howard, Robin
Abstract : Admission to the intensive care unit (ICU) is frequently required for the safe management of patients with anti-NMDA receptor encephalitis (NMDARE). Here, we present 22 patients (18 female, median age 28, range 17–59) with seropositive NMDARE, admitted to our neurological ICU between 2006- 18. Most commonly, patients were admitted following intubation and sedation for seizures/status epilepticus (7), depressed GCS (5), or agitation (2). Two were not intubated but admitted for monitoring, and four were admitted for plasma exchange (PLEX) only. Most were transferred to our centre for diagnostic work-up and specialist management. ICU-specific interventions included supervision of ventilation and respiratory weaning, and management of seizures. Autonomic dysfunction was frequent, including two patients with asystolic episodes on valsalva manoeuvres. Disease- specific treatments included IVIg, PLEX, steroids, rituximab and bortezomib. A teratoma was found in 9 women, including in two women who were also found to have another malignancy requiring treatment during admission. Length of ICU stay was frequently prolonged (median 66 days, range 4–457) with complex rehabilitation requirements on discharge. However, given sufficient recovery time, many returned to independence, and only three died. These data show the importance of good ICU care with specialised neurological input, to optimise outcomes in NMDARE.